Penguatan Ekowisata Berbasis Community Based Tourism (CBT) Desa Rowoboni Kabupaten Semarang - Amin, Syaiful; Atno Atno; Susilowati, Nurdian; Lusianto, Junaidi Fery; Subekti, Wildan; Riyanto, Muhammad Bagas; Prayoga, Teguh Irawan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This article discusses the strengthening of ecotourism based on Community-Based Tourism (CBT) in Rowoboni Village, Semarang Regency. The focus of this service is on optimizing the potential of natural tourism, particularly river and spring tourism, to improve the welfare of the local community. Through a holistic approach based on multidisciplinary research, this activity seeks to address issues related to the management and marketing of tourism, which are not yet optimal. The proposed solutions include strengthening the POKDARWIS institution, providing training for tourism management human resources, and developing digital-based marketing strategies. The results of this activity show an increase in the community's understanding and skills in managing and promoting ecotourism, although challenges remain in funding and responsiveness of tourism services. Overall, this service activity has successfully enhanced the ecotourism potential of Rowoboni Village.